2020
DOI: 10.1111/jai.14066
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niche of the Pacific Sierra (Scomberomorus sierra) in the southeastern Gulf of California: Assessing its importance as a predator and prey (Mesopredator) in the food web

Abstract: The identification of interspecific links (trophic niche) is important to characterize resource use of a predator, and to know its trophic role (for example, mesopredator or top predator) in the food web. In this study, we examined: a) the trophic ecology of Scomberomorus sierra as a predator (niche breadth, trophic overlap, and trophic position) and b) its presence as a prey in the diets of the region´s top predators, to evaluate the critical link of S. sierra as a probable mesopredator in the food web of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
1
3
1
Order By: Relevance
“…This could also indicate that the sources of carbon differ between both habitats, as estuarine organisms have increased assimilation of autochthon δ 13 C primary producers in the base of their food web, whilst large marine organisms reflect marine basal sources of δ 13 C, which are larger values when compared to estuarine and freshwater environments (Bouillon et al, 2008). The values found in our study are similar to other estuarine benthic feeders in the case of small juvenile organisms, and large nektonic predators, as in the case of large marine orangemouth weakfish (Torres‐Rojas et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could also indicate that the sources of carbon differ between both habitats, as estuarine organisms have increased assimilation of autochthon δ 13 C primary producers in the base of their food web, whilst large marine organisms reflect marine basal sources of δ 13 C, which are larger values when compared to estuarine and freshwater environments (Bouillon et al, 2008). The values found in our study are similar to other estuarine benthic feeders in the case of small juvenile organisms, and large nektonic predators, as in the case of large marine orangemouth weakfish (Torres‐Rojas et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The change in habitat is reflected in its diet, as small individuals prey on estuarine benthic and demersal fauna, and large organisms feed exclusively on nekton prey (squid and pelagic fish). This change in prey selection can be related to the development of the visual system, as well as changes in the energy requirements of the species' reproductive stages (Torres‐Rojas et al, 2020). It is known that body length plays a central role in predator–prey interactions (Sheldon et al, 1977), and the different isotopic composition of the transition from juvenile to adult orangemouth weakfish might be reflective of differences in feeding strategies associated with the increase in size and the change of habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, no significant differences were found for the P% and MI of Didymocylindrus filiformis Ishii, 1935 between the sexes of scombrid K. pelamis (Silva et al, 2017). Our results are surprising, because biological differences between males and females of S. sierra have not previously been reported in the literature (Aguirre-Villaseñor et al, 2006;Lucano et al, 2011;Espino-Barr et al, 2017;Justo & Kohn, 2014;Torres-Rojas et al, 2020). Thus, there is a clear indication of the prefer-ence of the parasites for one of the sexes of the host fish.…”
Section: Discussioncontrasting
confidence: 70%
“…However, all that has been published to date in the scientific literature does not show differences in the ecological relationships (habitat, behavior, and feeding) of males and females of S. sierra and does not help us to adequately explain the differences found between the sex of the host and the ecoparasitological parameters of T. crocea and Didymocylindrus sp. (Sandoval-Ramírez et al, 2020;Torres-Rojas et al, 2020). This interpretation would also apply the differences observed for the parasitological indices of (Iannacone et al, 2013;Rey et al, 2022).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation